Time Driven Activity Based Costing of Management Pathways for Vesicoureteral Reflux. Issue 1 (12th January 2021) - Raveendran, Lucshman; Bagli, Darius; O'Kelly, Fardod; DiCesare, Robert; Twardowski, Kornelia; During, David; Moretti, Myla E.; Koyle, Martin
Abstract: Introduction: The approach to the management of vesicoureteral reflux remains variable despite being a common pediatric diagnosis, which makes costing unpredictable. The aim of our study is to employ time driven activity based costing to characterize institutional costs of 3 management pathways for vesicoureteral reflux. Methods: We developed process maps for vesicoureteral reflux management based on practice guidelines applicable to a hypothetical female patient with vesicoureteral reflux index with grade 3 unilateral reflux without bowel bladder dysfunction at our institution. The costs of 3 management pathways were described, including watch and wait, minimally invasive endoscopic surgery with dextranomer/hyaluronic acid and open re-implantation surgery. Costs for each pathway were calculated using the capacity cost rate (/minute) for institutional resources and time estimates of resource use captured through direct observation and electronic medical record data. Clinical outcomes such as the breakthrough urinary tract infections or renal scarring were not addressed in this cost description. Results: A substantial range of total costs (CAD) was observed for all pathways including watch and wait (1, 683.58 to 2, 041.12), minimally invasive endoscopic surgery (2, 616.35 to 4, 012.89) and open re-implantation surgery (3, 317.76 to 3, 924.82). Total costs for a single dimercaptosuccinic acid scan accounted for 8% to 15% of any pathway's overall costs. Material costs for voiding cystourethrogram imaging and endoscopic surgery were high at 59% and 64% to 76% of their individual total costs, respectively. For open re-implantation surgery, high costs were attributable to the longer use of operating room space and inpatient postoperative stay. Conclusions: Time driven activity based costing demonstrates significant cost variability in vesicoureteral reflux treatment modalities and identified local cost drivers to target. Results from this study may be used to inform future cost-effectiveness analyses.